Pharmacokinetics of Human Red Blood Cell Microparticles Prepared Using High-Pressure Extrusion Method - Jy, Wenche; Rehni, Ashish K.; Bidot, Carlos; Navarro-Quero, Hever; Haase, Conner R.; Koch, Sebastian; Ahn, Yeon S.; Dave, Kunjan R. (Frontiers in Pharmacology, 2018)
Red blood cell microparticles (RMPs) are a high potency hemostatic agent, which may serve as a viable therapeutic approach. They generate thrombin in vitro and effective in arresting bleeding in animal bleeding models. However, prior to ascertaining the clinical efficacy of RMPs, detailed preclinical evaluation is necessary. Therefore, we aimed to characterize RMPs, ascertain their stability, and determine their pharmacokinetics in rats. RMPs were prepared from human RBCs by a high-pressure extrusion method. Pharmacokinetic parameters were computed from groups receiving various RMPs dosing regimens. Volume of distribution, elimination rate constant, and clearance for RMPs were also assessed. Major portion of prepared microparticles were RMPs and a very small portion of particles were from platelets and leukocytes. RMPs were stable when stored at 5 and -20°C for at least 12 months. In vivo half-life was found to vary for each paradigm, but in general, was less than 2 minutes for most of the paradigms evaluated. Our results demonstrate that RMPs are stable during prolonged storage and have a short half-life. Therefore, the clinical use of RMPs as a hemostatic agent, within a tailored treatment paradigm, may be advantageous in achieving prolonged systemic therapeutic benefit without provoking any thrombotic complications.